PENGEMBANGAN E-BOOK CERITA BERGAMBAR INTERAKTIF BERBASIS KEARIFAN LOKAL KULINER TRADISIONAL BALI PADA SISWA KELAS III SD - Ayu Puteri Susanthi, Ni Luh Gede; Margunayasa, I Gede; Kusuma Widiastuti, Ni Putu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low level of scientific literacy among elementary students and the limited use of interactive and contextual learning media, as reflected in the 2022 results of the Programme for International Student Assessment (PISA). The topic of energy in science learning remains abstract and insufficiently connected to students’ real-life experiences. This study aimed to develop a valid, practical, and effective interactive illustrated e-book based on Balinese traditional culinary local wisdom to improve third-grade students’ scientific literacy. The research employed a Research and Development method using the ADDIE model. The subjects were 31 third-grade students of SD Negeri 4 Panji. Data were collected through expert validation, teacher and student response questionnaires, and a scientific literacy test using a One-Group Pretest–Posttest design. Data were analyzed using a paired sample t-test. The results indicated that the e-book was very valid, highly practical (teacher 98.3%; students 98.88%), and effective with a significance value of <0.001. The findings imply stronger and improved scientific literacy for students.